In-situ Spectroscopic Techniques as Critical Evaluation Tools for Electrochemical Carbon dioxide Reduction: A Mini Review - Adarsh, K. S.; Chandrasekaran, Naveen; Chakrapani, Vidhya (Frontiers in Chemistry, 2020)
Electrocatalysis plays a crucial role in modern electrochemical energy conversion technologies as a greener replacement for conventional fossil fuel-based systems. Catalysts employed for electrochemical conversion reactions are expected to be cheaper, durable and have a balance of active centers (for absorption of the reactants, intermediates formed during the reactions), porosity and electrically conducting material to facilitate the flow of electrons for real-time applications. Spectroscopic and microscopic studies on the electrode-electrolyte interface, may lead to better understanding of the structural and compositional deviations occurring during the course of electrochemical reaction. Researchers have put significant efforts in the past decade towards understanding the mechanistic details of electrochemical reactions which resulted in hyphenation of electrochemical-spectroscopic/microscopic techniques. The hyphenation of diverse electrochemical and conventional microscopic, spectroscopic and chromatographic techniques in addition to the elementary pre-screening of electrocatalysts using computational methods have gained deeper understanding of the electrode-electrolyte interface in terms of activity, selectivity and durability throughout the reaction process. The focus of this mini review is to summarize the hyphenated electrochemical and non-electrochemical techniques as critical evaluation tools for electrocatalysts in CO2 reduction reaction.